Skeletal regeneration for segmental bone loss: Vascularised grafts, analogues and surrogates. (December 2021) - Dalisson, Benjamin; Charbonnier, Baptiste; Aoude, Ahmed; Gilardino, Mirko; Harvey, Edward; Makhoul, Nicholas; Barralet, Jake
Abstract: Massive segmental bone defects (SBD) are mostly treated by removing the fibula and transplanting it complete with blood supply. While revolutionary 50 years ago, this remains the standard treatment. This review considers different strategies to repair SBD and emerging potential replacements for this highly invasive procedure. Prior to the technical breakthrough of microsurgery, researchers in the 1960s and 1970s had begun to make considerable progress in developing non autologous routes to repairing SBD. While the breaktthrough of vascularised bone transplantation solved the immediate problem of a lack of reliable repair strategies, much of their prior work is still relevant today. We challenge the assumption that mimicry is necessary or likely to be successful and instead point to the utility of quite crude (from a materials technology perspective), approaches. Together there are quite compelling indications that the body can regenerate entire bone segments with few or no exogenous factors. This is important, as there is a limit to how expensive a bone repair can be and still be widely available to all patients since cost restraints within healthcare systems are not likely to diminish in the near future. Statement of Significance: This review is significant because it is a multidisciplinary view of several surgeons and scientists as to what is driving improvement in segmental bone defect repair, why many approaches to date have not succeeded and why some quite basic approaches can be as effective as they are. While there are many reviews of the literature of grafting and bone repair the relative lack of substantial improvement and slow rate of progress in clinical translation is often overlooked and we seek to challenge the reader to consider the issue more broadly. Graphical abstract: Image, graphical abstract